Review article "antifungal activity of black garlic (allium sativum linn) extract against candida albicans fungus" - Arip Saifurrohman; Yani Mulyani (Science Midwifery, 2026)
This study aims to analyze the effectiveness of black garlic extract (Allium satium Linn) on the growth of candida albicans fungus, which is known as an opportunistic pathogen in humans, black garlic produced through the process of heating garlic contains active compounds such as allicin, saponins, flavonoids and tannins that have the potential as antifungals. The method used in this study is a narrative review based on articles published in the last 10 years. The results show that black garlic extract can inhibit the growth of C. Albicans with a significant inhibition zone diameter at certain concentrations. In addition, black garlic has higher antioxidant activity than fresh garlic, making it a safe and effective alternative in the treatment of fungal infections, especially in the context of increasing antifungal resistance. This study recommends the formulation of black garlic in the form of a gel preparation as a safer and more effective preparation for applications in pharmaceutical preparations.